Prevention of Atrial Fibrillation using Vaughan Williams Class IC Drugs for Multiple Premature AtrialContractions: A Clinical Observational Study - Yamaguchi, Akira (Journal of Cardiology and Cardiovascular Medicine, 2024)
Background: Atrial fibrillation (A-Fib) poses a significant clinical challenge, particularly in the elderly and those with hypertension. If A-Fib represents one stage in the spectrum of electrical degeneration caused by aging-induced remodeling of the left atrial wall, catheter ablation is not an essential treatment. The efficacy of Vaughan Williams Class IC drug in preventing the progression of multiple premature atrial contractions (mPAC) toward paroxysmal atrial fibrillation (PAF) and A-Fib in the earlier stage of histological change was investigated. Method and results: Group A (4 patients with mPAC) and Group B (9 patients with PAF) were treated with Class IC drugs. Treatment outcomes were compared between these two Groups and Group C (8 patients with chronic A-Fib). Follow-up assessments were performed to evaluate the maintenance of sinus rhythm. All mPAC patients maintained sinus rhythm during the follow-up period. In the PAF group, 8 out of 9 patients maintained their sinus rhythm. Conclusion: Early treatment with Class IC drugs shows promise in preventing the progression of A-Fib and maintaining sinus rhythm in patients with mPAC and PAF. These findings highlight the potential role of pharmacological therapy in delaying the onset of A-Fib, thereby improving clinical outcomes and reducing the need for invasive procedures such as ablation.